2022
DOI: 10.3390/electronics11132016
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for the Classification of Butterfly Species Using Pre-Trained CNN Models

Abstract: In comparison to the competitors, engineers must provide quick, low-cost, and dependable solutions. The advancement of intelligence generated by machines and its application in almost every field has created a need to reduce the human role in image processing while also making time and labor profit. Lepidopterology is the discipline of entomology dedicated to the scientific analysis of caterpillars and the three butterfly superfamilies. Students studying lepidopterology must generally capture butterflies with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Although there are several public databases illustrating and grouping various common classes of insect pests, most of the authors used their own datasets in solving the problems specific (Bhoi et al, 2021;Rajeena et al, 2022). Creating proprietary databases for insect pest detection or monitoring using NNs can help improve the accuracy and specificity of pest detection systems, while also providing flexibility and cost-effectiveness (Segalla et al, 2020;Hong et al, 2021).…”
Section: Datasets Usedmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there are several public databases illustrating and grouping various common classes of insect pests, most of the authors used their own datasets in solving the problems specific (Bhoi et al, 2021;Rajeena et al, 2022). Creating proprietary databases for insect pest detection or monitoring using NNs can help improve the accuracy and specificity of pest detection systems, while also providing flexibility and cost-effectiveness (Segalla et al, 2020;Hong et al, 2021).…”
Section: Datasets Usedmentioning
confidence: 99%
“…Classification ACC: 75.3% -99.04% mAP: 71% (Ayan et al, 2020), (Fang et al, 2020), (Hansen et al, 2019), (Rajeena et al, 2022), (Sanghavi et al, 2022), (Singh et al, 2021), , (Liu et al, 2022) Inception ResNetv2 Detection ACC: 91.14% (Khanramaki et al, 2021), (Singh et al, 2021) LeNet et al, 2021), (Hong et al, 2021), (Nanni et al, 2022), (Rajeena et al, 2022), (Xing et al, 2019) (Ahmad et al, 2021), (Alsanea et al, 2022), (Butera et al, 2021), (Du et al, 2022), (Guo et al, 2021), (Hong et al, 2021), (Li et al, 2019), (Liu et al, 2019), (Wang et al, 2022), (Shi et (Butera et al, 2021), (De Cesaro Juńior et al, 2022), (Fang et al, 2020), (Dai et al, 2021), (Khanramaki et al, 2021), (Li et al, 2019), (Liu et al, 2019), (Liu et al, 2022), (Malathi and Gopinath, 2021), (Nanni et al, 2022), (Rajeena et al, 2022), (Sanghavi et al, 2022), , (Wang et al, 2022), (Xu et al, 2022) ResNet 53 Detection mAP: 77.29% (Lv et al, 2022) ResNet 101 Detection mAP: 85.53% -99.5%…”
Section: Inception V3mentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al [77] proposed a novel neural network architecture for encoding and synthesizing 3D shapes. The authors discussed transfer learning-based neural network models for the identification of butterfly species in Rajeena et al [78]. Ghayvat et al suggested a strategy that combines a blockchainbased nondisclosure method with a two-step authentication architecture and an elliptic curve cryptography-based cryptographic signature framework.…”
Section: Wireless Communications and Mobile Computingmentioning
confidence: 99%
“…Image classification is the process of categorizing images into one of several predetermined categories. A single image can be classified into an endless number of categories [1]. Manually evaluating and classifying these images can be time-consuming, especially when there are a big number of them; therefore, automating the process using machine learning and deep learning techniques would be quite beneficial.…”
Section: Introductionmentioning
confidence: 99%